2006
DOI: 10.1111/j.1745-4506.2006.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer knowledge and expectations of restaurant menus and their governing legislation: a qualitative assessment

Abstract: Many consumers feel that it is the social responsibility of restaurants to inform them of the nutritional content of food items that may be detrimental to their health or contrary to their beliefs. Current legislation, through the Truth-in-Menu Law, protects consumers from misleading advertisements, but does not mandate that restaurant establishments provide nutritional information. This qualitative study aims to assess how much consumers really know about menu labeling legislation and what information they co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 17 publications
2
46
0
2
Order By: Relevance
“…Consistent with the results observed in this study, Thomas and Mills (2006), in a study about nutritional information in restaurants, found that many consumers feel that it is the responsibility of restaurants to inform them about the nutritional content of foods that can be harmful to their health or contrary to their beliefs.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with the results observed in this study, Thomas and Mills (2006), in a study about nutritional information in restaurants, found that many consumers feel that it is the responsibility of restaurants to inform them about the nutritional content of foods that can be harmful to their health or contrary to their beliefs.…”
Section: Discussionsupporting
confidence: 80%
“…Given that these individuals have developed a comfort level treating their condition with medication or otherwise coping with the condition, these individuals feel there is limited risk involved with their current dietary practices. These individuals desire to know if the food they are consuming is healthy but do not alter their diets because of this information (Thomas and Mills, 2006). Although they acknowledge they have numerous chronic conditions, the majority of these individuals rate their health as above average (Thomas et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Azrina et al (2011) defines consumer "as any individuals or households utilizing good and services generated within the economy." Many studies show that consumers' awareness and knowledge impose significant impact on various types of effective consumers' behaviors (McEachern & Warnaby 2008;Hartlieb & Jones 2009;Liang & Xianyu 2008;Donoghue & de Klerk, 2009;Thomas & Mills 2006;Chartrand 2005;Coulter et al 2005;and Dommeyer & Gross 2003). For example, Hartlieb and Jones (2009) emphasizes the importance of ethical labeling for humanizing business images.…”
Section: Introductionmentioning
confidence: 99%